The FIP-1 like polyadenylation factor in trypanosomes and the structural basis for its interaction with CPSF30 - Bercovich, Natalia (2009)
In trypanosomes transcription is polycistronic and individual mRNAs are generated by a trans-splicing/polyadenylation coupled reaction. We identified a divergent trypanosome FIP1-like, a factor required for mRNA 3′ end formation from yeasts to human. Here we showed that it is a nuclear protein with a speckled distribution essential for trypanosome viability. A strong interaction was found between TcFIP1-like and TcCPSF30, a component of the polyadenylation complex. We determined the specific amino acids in each protein involved in the interaction. Significant differences were found between the trypanosome interaction surface and its human counterpart. Although CPSF30/FIP1 interaction is known in other organisms, this is the first report mapping the interaction surface at the amino acid level.